Parametric Study of the Dynamic Along-Wind Response of a Guyed Tower - Ballaben, Jorge S. (2012)
As wireless communications spread, there is an increasing demand for antenna supportingstructures. Lattice towers are commonly used systems, either self-supported or guyed. The latter arechosen for economical reasons when there is enough space for their location. Radio and television em-ploy structures that range between 100 and 600 m and communication towers for mobile phones arearound 60 m though higher structures are also constructed. For large heights, guyed masts are indi-cated. However, it depends on the customer preferences, suppliers, budget and location. Generally,self-supported structures are preferred in urban areas and guyed masts in the countryside. Nowadays thedemand for more accurate and reliable communication systems poses higher structural demands sincethe signal technology sometimes requires of very small motions of the supporting structures to achieve ahigh quality transmission. The design of these structures is, in general, carried out following the standardcodes and simplified models. The dynamic actions, as wind and earthquakes, are not addressed in detailwith exception of special cases, despite the large potential of adverse impact. Guyed structures stiffnessare highly dependent on the guys tension. The influence of this parameter is relevant to the dynamicresponse. Also, the mast stiffness and damping are variables of interest. In this work, the dynamic re-sponse of a communication lattice guyed tower is analyzed under wind loads and the degree of influenceof the mentioned parameters is assessed